Pretty Guardian: Sailor Moon - Book 2 2 - Takeuchi, Naoko (New York : Kodansha Comics, 2011)
"Usagi Tsukino is a normal girl until she meets up with Luna, a talking cat, who tells her that she is Sailor Moon. As Sailor Moon, Usagi must fight evils and enforce justice, in the name of the Moon and the mysterious Moon Princess. She meets other girls destined to be Sailor Senshi (Sailor Scouts), and together, they fight the forces of evil"--Publishers website.
"First published in Japan in 2003 by Kodansha Ltd., Tokyo, as Bishoujosenshi Sailor Moon Shinsoban, volume 2"--T.p. verso.
"A Kodansha Comics trade paperback original"--T.p. verso.
"T Ages 13+"--P. [4] of cover.
Keywords: Sailor Moon -- (Fictitious character) -- Fiction; Teenage girls -- Fiction; Women heroes -- Fiction; Superheroes -- Fiction; Magic -- Fiction; Good and evil -- Fiction; Manga